Glandular dots of Caesalpinia echinata Lam. (Leguminosae): Distribution, structure and ultrastructure - Teixeira, Simone de Pádua; Machado, Sìlvia Rodrigues [UNESP] (Torrey Botanical Society, 2007)
The structure and ultrastructure of immature to fully mature glandular dots in the leaf, floral organs and fruit, and their secretion components were described in Caesalpinia echinata Lam. (Leguminosae) for the first time. Data showed that glandular dots were groups of idioblasts with contents that reacted positively for both lipophilic and hydrophilic substances. Idioblasts originated from successive divisions of the ground meristem cells or mesophyll cells of an ovary of a fertilized flower. Following division, cells enlarged, the cytoplasm became denser and its content became full. No idioblasts were observed after fruit sclerification. Besides these mixed-content idioblasts, some cells in the sepals, petals and mesocarp were found to contain phenolic compounds, which probably represent a kind of constitutive defense mechanism, once the flowers and fruits become highly fitness-valued parts of the plant and can be commonly attacked. The contents of the idioblasts are released as the growth rate of the embryo increases, indicating that the plant probably diverts the precursors of secondary metabolites into the primary metabolism, at this critical time of embryo development.
Keywords: Anatomy; Brazil wood; Histochemistry; Idioblasts; Leguminosae; anatomy; fitness; legume; metabolism; phenolic compound; population distribution; population structure; ultrastructure; Brazil; South America; Caesalpinia; Caesalpinia echinata; Fabaceae